2023
DOI: 10.7759/cureus.34722
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting: Benefits, Side Effects, Quality of Life, and Knowledge of the Saudi Population

Abstract: ConclusionThe IF diet is an efficient dietary plan for those aiming at a weight loss journey over a short duration, ranging from less than a month up to three months. Minimal side effects were found during fasting, being of different intensities, which did not need surgical or medical treatment. All in all, most of our respondents were pleased with their experience and saw excellent weight loss results using the IF diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Intermittent Fasting also carried risk of hypoglycemic episodes leading to unconsciousness, vertigo and trembling heartbeat etc. We also found that beneficial effects of intermittent fasting was associated with the marital status, qualification and family history of the patients, while no association was found with gender and age and it is also shown by some other published literature (16,17).…”
Section: Discussionsupporting
confidence: 75%
“…Intermittent Fasting also carried risk of hypoglycemic episodes leading to unconsciousness, vertigo and trembling heartbeat etc. We also found that beneficial effects of intermittent fasting was associated with the marital status, qualification and family history of the patients, while no association was found with gender and age and it is also shown by some other published literature (16,17).…”
Section: Discussionsupporting
confidence: 75%
“…CCRD showed a positive impact on general health, better energy levels, and fewer role limitations due to physical health compared to TRIF. A study investigating the benefits, side effects, and knowledge of Intermittent Fasting among the Saudi population noted common side effects like headache, lethargy, mood swings, and dizziness [ 30 ]. Therefore, our results support these findings but from the perspective of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…A study examining 147 individuals with a high BMI following an intermittent fasting regimen revealed common adverse effects, including headache (61.3%), lethargy (68%), mood changes (57.8%), and dizziness and polyuria (55.8 and 46.2%, respectively) ( 37 ). Headache, a prevalent side effect during fasting, is often attributed to hypoglycemia and manifests as a diffuse, non-pulsating headache.…”
Section: Introductionmentioning
confidence: 99%
“…Headache, a prevalent side effect during fasting, is often attributed to hypoglycemia and manifests as a diffuse, non-pulsating headache. It is crucial to acknowledge these potential risks and side effects associated with intermittent fasting to ensure safe and informed implementation of this dietary approach ( 37 , 38 ). On the other hand, various studies have evaluated the benefits of intermittent fasting and have found significant results, including reductions in glucose and insulin levels, as well as notable weight loss and decreased BMI ( 39–41 ).…”
Section: Introductionmentioning
confidence: 99%